Continuously Tuning Distributed Bragg Reflector Erbium Doped Fiber Laser - Tam, Tran Thi; Cham, Vu Ngoc; Trung, Dang Quoc; Vu, Tran Anh; Minh, Le Huu (Communications in Physics, 2008)
The linear configuration single-mode Distributed Bragg Reflection (DBR) Erbium doped Fiber laser has been tested. The cavity length of the laser utilizing intracore Bragg reflectors, no longer than one centimetre and the grating bandwidth is below ~ 0.2 nm. The 1.55-$μ$m emission wavelength of the laser can be continously tuned within 2 nm.